Acupuncture alleviates acid‐ and purine‐induced pain in rodents. (21st November 2019) - Zhang, Ying; Huang, Lumei; Kozlov, Sergey A.; Rubini, Patrizia; Tang, Yong; Illes, Peter
Abstract : Background and Purpose: We set out to investigate the effects of electroacupuncture (EAP) and moxibustion on pain states mediated by a range of acid‐ and ATP‐sensitive nociceptors in acute and inflammatory rodent pain models. Experimental Approach: We injected PBS (pH 6.0 or 4.0) or α, β‐methylene ATP into the paw of rats or mice to cause thermal hypersensitivity, which was quantified by the paw withdrawal latency (PWL). Inflammatory pain was induced by the injection of complete Freund's adjuvant (CFA) into the rat paw. Key Results: EAP and moxibustion counteracted the decrease of PWL mediated by acid‐sensing ion channel 3 (ASIC3) and transient receptor potential vanilloid 1 (TRPV1) channels in response to pH 6.0 PBS, but not that mediated by TRPV1 channels only, initiated by the injection of pH 4.0 PBS. Similarly, EAP and moxibustion prevented the purinergically induced pain which was caused by stimulation of P2X3 (P2X2/3) and P2X7 receptors. The effect of CFA was also relieved by EAP and moxibustion. Conclusions and Implications: During acute thermal pain and CFA‐induced inflammatory pain, ASIC3/TRPV1 channels and P2X3/P2X7 receptors are activated by protons and exogenous α, β‐methylene ATP or endogenously released ATP respectively. Low‐threshold acute acidic pain mediated by the activation of ASIC3/TRPV1 channels was reversed by EAP/moxibustion, while high‐threshold acidic pain that is mediated exclusively by the activation of TRPV1 channels was not. ASIC3 and P2X3 receptors appear to interact with each other in responding to both protons and ATP, by forming an ASIC3/P2X3 "cognate receptor", sensitive to EAP/moxibustion.